Expert Consensus on Key Points for Inpatient Rehabilitation Treatment Documentation - Physical Therapy Committee of Rehabilitation Medicine; Professional Occupational Therapy Committee of Chinese Association of Rehabilitation Medicine (康复学报)
Standardized rehabilitation treatment documentation is great significance to the clinical work of rehabilitation. At present, there is no “standard for the writing of rehabilitation treatment documents” for reference, which will greatly affect the standardization and homogenization of rehabilitation treatment. The development of the Expert Consensus on the Key Points of Inpatient Rehabilitation Treatment Documentation helps to provide a clear and operable standard for rehabilitation healthcare professionals to promote the standardization of the writing of rehabilitation treatment documents. This Expert Consensus puts forward standardization suggestions in 3 aspects: basic principles, basic elements, and main contents of inpatient rehabilitation treatment documentation. The writing of rehabilitation treatment documents should follow the principles of standardization, comprehensiveness, objectivity, accuracy, timeliness, compliance and authenticity. The basic writing elements should include the initial record, the treatment process record and the discharge record, and it is recommended that the subjective information, objective information, assessment and planning (SOAP) medical record writing model be used as the basic format. The subjective information in the initial record should include the chief complaint, current medical history, past history, social history, emotion or attitude, pain and expectation of rehabilitation; the objective information in the initial record should include the basic vital signs, state of consciousness, mental and psychological state, and the assessment results of physical therapy, occupational therapy, speech and swallowing therapy according to the actual situation; the assessment and analysis should include the functional diagnosis, the long term rehabilitation goal and the short term rehabilitation goal; the treatment plan should include the content of treatment and other precautions. Records of the treatment process should include implementation records and progress records. Discharge records should include discharge diagnosis, discharge rehabilitation evaluation, next stage goals, discharge guidance plan. This expert consensus can improve the writing quality of inpatient rehabilitation treatment documentation; promote the standardization and homogenization of China's rehabilitation treatment clinical work; and provide support and basis for clinical and scientific research work in rehabilitation treatment. It is applicable to guide the rehabilitation therapists in the rehabilitation wards of general hospitals, rehabilitation hospitals, and wards of community recreational institutions to standardize the writing of rehabilitation treatment documentation.